2021
DOI: 10.20944/preprints202105.0766.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 Antibodies Among Homeless People Living Rough, in Shelters and Squats: A Large Population-Based Study in France

Abstract: Background: Overcrowded housing, as well as inadequate sanitary conditions, contribute to making homeless people particularly vulnerable to the SARS-CoV-2 infection. We aimed to assess the seroprevalence of the SARS-CoV-2 infection among people experiencing homelessness on a large city-wide scale in France, taking into account different community settings. Methods: A consortium of outreach teams in 48 different locations including streets, slums, squats, emergency or transitional shelters and drop-in centres p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…), physical items in the building being touched permanently (door handles, furniture, common TV rooms). Effectively, we observed statistically higher rates of infection in emergency shelters in our seroprevalence study (Loubière et al, 2021), consistent with other studies in emergency shelters (Dubost et al, 2020;Kirby, 2020). In spite of a good application of barrier measures in emergency shelters, the density and organization of such places do not permit the protection of the people accommodated from COVID-19, as was correctly perceived by interviewees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…), physical items in the building being touched permanently (door handles, furniture, common TV rooms). Effectively, we observed statistically higher rates of infection in emergency shelters in our seroprevalence study (Loubière et al, 2021), consistent with other studies in emergency shelters (Dubost et al, 2020;Kirby, 2020). In spite of a good application of barrier measures in emergency shelters, the density and organization of such places do not permit the protection of the people accommodated from COVID-19, as was correctly perceived by interviewees.…”
Section: Discussionsupporting
confidence: 90%
“…The quantitative study design and sample size has been described elsewhere (Loubière et al, 2021). In brief, participants were enrolled between June 1 and August 5, 2020.…”
Section: Samplementioning
confidence: 99%
“…The proportion of past infection (i.e. SARS-CoV-2 2 antibodies) in our study was also substantially lower than found in other countries such as France (22,23). A cross-sectional study conducted during the lockdown of the rst wave in Paris, SARS-CoV-2 seroprevalence ranged from 28% to 89% among 818 PEH and was highest among PEH who lived in densely populated worker residences (22).…”
Section: Discussioncontrasting
confidence: 64%
“…A cross-sectional study conducted during the lockdown of the rst wave in Paris, SARS-CoV-2 seroprevalence ranged from 28% to 89% among 818 PEH and was highest among PEH who lived in densely populated worker residences (22). Another community-based study in June 2020 among 1,156 PEH in Marseille, France showed antibody positivity ranging from 2.2% in people who lived on the streets to 8.1% in people living in emergency shelters (23), which is more in line with our ndings. Considering the mixed results from these studies, SARS-CoV-2 (sero-)prevalence needs to be evaluated with at a country-speci c level and monitored at different timepoints among PEH.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence from the early COVID-19 waves suggests that population subgroups, such as people experiencing homelessness (PEH) or precariously housed (PH), are disproportionately exposed to infection [1-3] and the severe forms of disease [4-6], as well as suffering from greater mental health and social impacts [7]. Transmission risk is worsened by factors specific to these groups, such as precarious living conditions, high population density, need to access food distribution services, poor access to sanitation and hygiene, and difficulties accessing care [1, 2, 3, 5, 7]. COVID-19 prevention measures such as social distancing and self-isolation are challenging to maintain for such groups [1, 3, 5].…”
Section: Introductionmentioning
confidence: 99%